Literature Study: Analysis of Gratitude Factors in Individuals - Abd. Hamid Cholili; Alifah Aulia Putri Difayanti; Evin Yusmafati (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The research aims to determine the influencing factors of gratitude in individuals as human beings. This research uses the literature study method to look for aspects that influence gratitude in individuals, using a data accumulation scheme through Google Scholar and Science Direct to access journals and scientific papers. A literature search was carried out with the keywords